2007
DOI: 10.1161/hypertensionaha.107.087890
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy, Subclinical Atherosclerosis, and Inflammation

Abstract: Abstract-To elucidate mechanisms by which left ventricular (LV) hypertrophy (LVH) increases the risk of atherosclerotic heart disease, we sought to determine whether LVH is independently associated with coronary artery calcium (CAC) and serum C-reactive protein (CRP) levels in the general population. The Dallas Heart Study is a population-based sample in which 2633 individuals underwent cardiac MRI to measure LV structure, electron beam CT to measure CAC, and measurement of plasma CRP. We used univariate and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 63 publications
4
46
2
3
Order By: Relevance
“…However, we believe we covered typical times for routine practice. Fourth, the levels of CRP and ESR are influenced by the presence of systemic conditions [6,9,18,24]. In our study, we found no differences in the prevalence of the systemic conditions between the unilateral and staged bilateral groups.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…However, we believe we covered typical times for routine practice. Fourth, the levels of CRP and ESR are influenced by the presence of systemic conditions [6,9,18,24]. In our study, we found no differences in the prevalence of the systemic conditions between the unilateral and staged bilateral groups.…”
Section: Discussioncontrasting
confidence: 47%
“…The data on the fortysecond and ninetieth postoperative days only were compared between the unilateral and the second knee bilateral groups. Because the levels of CRP and ESR are influenced by the presence of other systemic conditions (diabetes mellitus, cardiac diseases, chronic lung and kidney disease, and cancers) [6,9,18,24], proportions of patients with the systemic conditions were compared between the unilateral and the staged bilateral groups. There were no differences in the prevalence of systemic conditions between the unilateral and staged bilateral groups (20.3% versus 27.9%; p [ 0.05, chi square test).…”
Section: Methodsmentioning
confidence: 99%
“…The myocardial thickness and Describe cut-off points: CT stenosis, C70% coronary stenosis by CCTA; Resting CTP, C30 of likelihood (%) of having a perfusion defect; significant ischemia, B0.8 by invasive fractional flow reserve PPV, positive predictive value; NPV, negative predictive value; CT, computed tomography; CTP, computed tomography perfusion ratio of subendocardium perfusion to subepicardial perfusion are easily obtainable parameters when performed using CTP analysis and are closely related to ischemia. Indeed, previous data suggest that a high myocardial thickness is associated with atherosclerotic burden and elevated inflammatory activity, 29 and was found to be an independent predictor of adverse events in addition to coronary atherosclerosis and myocardial ischemia. 30 It is also well known that there are significant relationships between the subendocardium-tosubepicardial perfusion ratio and ischemia.…”
Section: Discussionmentioning
confidence: 97%
“…накопилось значительное число наблюдений, которые свидетельствуют в пользу участия факторов, традиционно относимых к сис-теме воспаления, в развитии гипертрофии левого желудочка. В популяционных исследованиях выяв-лена ассоциация уровня С-реактивного белка (СРБ) и толщины стенки левого желудочка [1], механизм которой неясен -обнаружено, что ГМЛЖ может предсказывать при длительном наблюдении последу-ющее повышение СРБ [2]. Найдены эксперименталь-ные подтверждения участия интерлейкина-6 (ИЛ-6) и фактора некроза опухоли альфа в развитии ГМЛЖ [3].…”
Section: Discussionunclassified
“…Есть данные об ассоциации уровня СРБ c уровнем АД и развитием ГМЛЖ [1]. Биохимической основой для взаимосвязи между развитием ГМЛЖ и уровнем СРБ является то, что, стимулируя синтез адгезивных молекул и матрикс-ных металлопротеиназ, СРБ активирует тучные клетки, которые могут синтезировать факторы роста и потенцировать развитие фиброза миокарда.…”
Section: Discussionunclassified